Pengaruh Self-Efficacy, Tekanan Waktu Auditor Terhadap Kualitas Audit Dengan Etika Profesi Sebagai Variabel Moderasi - Lina Pratama; Syaiful Syaiful (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Auditing is an examination process that is carried out critically and systematically. In this process, the party conducting the audit must be independent of the financial statements. Companies really need auditor services, because auditors have an important role in preventing fraud. The profession of an auditor is an individual who focuses on auditing activities. They work to audit various financial-related reports from institutions, agencies, or companies. In carrying out the audit process, auditors always examine the financial data contained in the financial statements. This research is a quantitative study with a survey method conducted at the Surabaya Public Accounting Firm, involving auditors from 47 KAP offices. This study uses a Structural Equation Model (SEM) approach based on Partial Least Square (PLS) to test the relationship between variables. The table indicates that the self-efficacy variable has a significant effect on audit quality. In addition, auditor time pressure also has a significant effect on audit quality. However, the moderating variable of professional ethics cannot moderate the relationship between self-efficacy and auditor time pressure and audit quality significantly.